The Godfather part III - Coppola, Francis Ford 1939-; Pacino, Al 1940-; Puzo, Mario 1920-1999; Keaton, Diane; Garcia, Andy (Paramount Home Video, 2002)
The Godfather part III continues the Corleane family history in 1979, as the sins of the parents are visited upon the children. Despite every attempt to go legit, to become respectable, the past cannot be silenced. The family has amassed unimaginable wealth, and as the film opens Michael Corleone(Al Pacino) is being invested with a great honor by the church. Later that day, at a reception, his daughter announces a Corleone family gift to the church and the charities of Sicily, " a check in the amount of USD100 million." But the Corleones are about to find, as others have throughout history, that you cannot buy forgiveness. Sure, you can do business with evil men inside the church, for all men are fallible and capable of sin. But God does not take payoffs.